2022
DOI: 10.3389/fendo.2022.1014670
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for the improvement of metabolic profiles in patients with metabolic-associated fatty liver disease: A systematic review and meta-analysis of randomized controlled trials

Abstract: ObjectiveThis meta-analysis of randomized controlled trials (RCTs) was conducted to assess the efficacy of probiotics in the treatment of metabolic-associated fatty liver disease (MAFLD) mainly in terms of liver function, glucose and lipid metabolism, and inflammation.MethodsRCTs were searched on PubMed, Web of Science, Embase, and the Cochrane Library until June 2022. A meta-analysis was performed on the therapeutic efficacy of probiotics on liver function, glucose and lipid metabolism, and inflammatory bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Among a total of 772 patients, the use of probiotics for therapeutic purposes could reduce the levels of alanine aminotransferase (mean difference (MD): −11.76 (−16.06, −7.46), p < 0.00001), aspartate aminotransferase (MD: −9.08 (−13.60, −4.56), p < 0.0001), γ-glutamyltransferase (MD: −5.67 (−6.80, −4.54), p < 0.00001) and homeostasis model assessment of insulin resistance (MD: −0.62 (−1.08, −0.15), p = 0.01) in patients with MAFLD, compared to control patients. Indeed, this study did not show statistical significance for levels of total cholesterol, triglycerides, low-density lipoproteins (LDL), C-reactive protein (PCR), and tumor necrosis factor-α (TNF-α) [ 95 ]. Regarding prebiotics, their use, in combination with probiotics, is recommended, as suggested by a recent review that underlines the importance of this combined approach that showed a significant reduction in the levels of hepatic steatosis, alanine aminotransferase (ALT), AST, HDL, LDL, triglyceride and cholesterol levels in 782 MAFLD patients compared to healthy controls [ 96 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Among a total of 772 patients, the use of probiotics for therapeutic purposes could reduce the levels of alanine aminotransferase (mean difference (MD): −11.76 (−16.06, −7.46), p < 0.00001), aspartate aminotransferase (MD: −9.08 (−13.60, −4.56), p < 0.0001), γ-glutamyltransferase (MD: −5.67 (−6.80, −4.54), p < 0.00001) and homeostasis model assessment of insulin resistance (MD: −0.62 (−1.08, −0.15), p = 0.01) in patients with MAFLD, compared to control patients. Indeed, this study did not show statistical significance for levels of total cholesterol, triglycerides, low-density lipoproteins (LDL), C-reactive protein (PCR), and tumor necrosis factor-α (TNF-α) [ 95 ]. Regarding prebiotics, their use, in combination with probiotics, is recommended, as suggested by a recent review that underlines the importance of this combined approach that showed a significant reduction in the levels of hepatic steatosis, alanine aminotransferase (ALT), AST, HDL, LDL, triglyceride and cholesterol levels in 782 MAFLD patients compared to healthy controls [ 96 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…The most commonly used probiotics that tend to be effective include Lactobacillus and Bifidobacterium, along with Lactococcus, Streptococcus, Enterococcus, and Bacillus. 32 A combination of probiotics with Omega-3 has demonstrated decreases in hepatic steatosis in prospective human studies, as opposed to probiotic or Omega-3 treatment alone. Furthermore, Omega-3 treatment with probiotics has been shown to reduce hepatic de novo lipogenesis by inactivating sterol regulatory element-binding protein-1v (SREBP1v) and carbohydrate-responsive element-binding protein (ChREBP) activity and also reducing inflammation.…”
Section: Probioticsmentioning
confidence: 99%
“…In recent years, mounting research has focused on the gut-liver axis and found that the intestinal mucosal barrier, gut microbiota, and its metabolites are closely related to NAFLD pathogenesis [ 12 ]. Therefore, appropriate supplementation of specific probiotics can affect the liver’s metabolic function and slow down NAFLD severity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%